An evaluation on the implementation of green neighbourhood initiatives towards sustainable urban living in Subang Jaya, Malaysia / Rohana Ramli - Ramli, Rohana (2023)
In an era of globalisation and hyper-urbanisation, cities are rapidly emerging as drivers of social, economic, and environmental change. The current global climate change brings the need for serious, in designing urban development. One of the concepts that have been introduced for sustainable city formation is the Green Neighbourhood Initiative (GNI). Green neighbourhood is a neighbourhood that practices as a way of life to meet the needs of people's activities, regulate pollution, save energy, accessibility, safeguard the environment, increase employment opportunities, and reduce crime rates. Conflicts between rapid development and local communities required a new paradigm to understand about the relationships between green neighbourhood initiatives of communities and Local Authority (LA). Academic literature in key areas of urban sustainability, green cities, urban living, neighbourhood concept and green neighbourhood initiatives elements planning guides the theoretical framework. The aim of this research is to evaluate on the implementation of green neighbourhood initiatives towards sustainable urban living. The case study is the Subang Jaya City Council. The scope and limitation in the implementation of green neighbourhood initiatives are to investigate the current practices of green neighbourhood initiatives, to analyse the effectiveness, to evaluate the challenges and benefits, to evaluate the planning factors contributing green neighbourhood and to develop strategies and framework on implementing green neighbourhood initiatives. The methodology applied was a mixed-method of qualitative, quantitative, spatial and observation analysis. The qualitative research involved the experts survey from LA officers and related agencies via face-to-face interview. The quantitative research involved the community reception with 400 respondents to examining the case study consisted of four (4) neighbourhood areas in Subang Jaya City Council namely is USJ 5, USJ 6 and USJ10, SS14 and SS18, Bandar Sunway and Putra Heights. The analysis of qualitative data is by contents and thematic analysis. Meanwhile, for quantitative data analysis using SPSS to identify relationships between the communities' satisfaction. The findings showed that the implementation of green neighbourhood initiatives in urban living concerned is not fully ready and suggested for improvement strategies with communities' satisfaction. The research recommended a framework and strategies for the implementation of green neighbourhood initiatives by Local Authorities include educating and promoting green neighbourhood initiatives in multi-level development, identifying new urban living indicators and guidelines. The implementation of green neighbourhood initiatives must be reviewed and to continue with the improvement. The recommendations of the research can provide a good reference for other Local Authorities.